Analyzing Gender Differences of Entrepreneurial Intention Among Student in Islamic University Malang - Nur Hidayati; Afi Rachmat Slamet; Iin Agustina (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Research on entrepreneurial intention has been widely studied before, with the majority of research focusing on factors that drive individual intentions to become entrepreneurs. This study aims to examine and answer research questions about whether there are differences between male and female students in terms of their interest in entrepreneurship. Design/methodology/approach: The unidimensional nature and non-causality in this study are interesting things to further explore the depth of the research phenomenon. The entrepreneurial intention instrument with 7 indicators was developed in this study to capture the perceptions of students in assessing their intention in becoming entrepreneur. A total of 78 students from the faculty of economics and business were the respondents who participated in this study, with 40 males and 38 females. Findings: The results of the study reveal that of the seven indicators that reflect entrepreneurial intention, there are three indicators that show significant differences between male and female students in their interest in entrepreneurship, in which consist of (1) planning for starting a business, (2) feeling of being able to start their own business in the next few years, and (3) serious thinking about starting a business in the future. Research limitations/implications: By knowing about gender differences in perceiving intentions for entrepreneurship, relevant stakeholders can contribute to strengthening entrepreneurial values in students. Practical implications: The research findings draw attention to how this is the basis for how to encourage student interest in the Faculty of Economics and Business, especially in setting entrepreneurship as professional goal that could be chosen by students. University can accommodate it in the form of policies such as the "free campus" curriculum which allows students to explore and dig deeper about their interests and develop the capacity to become entrepreneurs and make it their main profession in the future. Originality/value: This study seeks to reveal how the differences in the entrepreneurial intentions of students studying at Islamic Universities. Paper type: Research Paper